Strategi Open Ended dalam Meningkatkan Kemampuan Berpikir Kreatif Siswa pada Pembelajaran Tematik - Asep Ediana Latif; Desi Ayu Lestari (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2020)
This study aims to determine the application of open ended strategies can improve students' creative thinking abilities. The research method used in this study is the classroom action research (CAR) method using the Kurt Lewin model consisting of four components namely, planning, action, observation and reflection. The research subjects were 45 students of MI Al-Khoiriyah Sawangan class of students. Data collection techniques used were observation sheets, interviews and documentation. Data analysis was performed in a qualitative description. Based on the results of the first cycle study 63% of students stated to have the ability to think creatively, in the second cycle 88% of students have the ability to think creatively. This achievement shows that the use of open ended strategies can improve students' creative thinking skills in thematic learning.  Keywords: Creative thinking ability, open ended, thematic learning, elementary school